2018
DOI: 10.5751/es-10004-230239
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic relationship between sense of place and risk perception in landscapes of mobility

Abstract: ABSTRACT. Coastal areas are exposed to changing patterns of mobility and increasingly extreme weather events, offering unique opportunities to study the complexity of adaptation to global changes and the diversity of responses to risk. How individuals and communities respond to risk varies widely, however traditional rationalist and economic based understandings have proved limited in explaining responses to risk. Increasingly social science, and specifically, a focus on peoples' relationships with their local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 57 publications
1
26
0
1
Order By: Relevance
“…To host migrants from North Africa and later to attract new populations (retirees, tourists, entrepreneurs), wetlands were drained, mosquito populations eradicated, rivers controlled with dams and dykes, transport infrastructures constructed and new urban settlements continually in development. Here, place, identity and relationships with nature have been mobilized into political struggles and narratives around nature, infrastructure and place have developed (Quinn et al, 2018). Empathy is evoked through these narratives, giving agency to and emotion -for example, flood or mosquito blooms expressed as anger.…”
Section: The New Normal -Disruptions To Place and Identities And The mentioning
confidence: 99%
“…To host migrants from North Africa and later to attract new populations (retirees, tourists, entrepreneurs), wetlands were drained, mosquito populations eradicated, rivers controlled with dams and dykes, transport infrastructures constructed and new urban settlements continually in development. Here, place, identity and relationships with nature have been mobilized into political struggles and narratives around nature, infrastructure and place have developed (Quinn et al, 2018). Empathy is evoked through these narratives, giving agency to and emotion -for example, flood or mosquito blooms expressed as anger.…”
Section: The New Normal -Disruptions To Place and Identities And The mentioning
confidence: 99%
“…Most of the existing literature on migrations related to earthquake risk or damage has tended to account for evidence of population movements by focusing on individual socioeconomic contexts and disparities in regional development; however, the diversity of regional characteristics and the complexity of the factors at play make a single overarching explanation difficult to achieve (M. Hori, Schafer, & Bowman, 2009). In France, researchers have attempted to construct a conceptual model to predict how population movements might be impacted by coastal residents' cognitive awareness of increased disaster risk related to climate change (Quinn et al, 2018). Studies have demonstrated how regional attachment has both positive and negative influences on risk perception (Ruiz & Hernandez, 2014), such that those who have a strong attachment to an area are particularly reluctant to leave even in a case of disaster (Bonaiuto et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to these factors, sense of place and individual socio-economic characteristics are also crucial elements able to influence pre-emptive disaster actions. Sense of place reflects attitudes and behaviour in epistemological understandings of social and ecological change and humanenvironment relationships (Quinn et al 2018). Sociocultural factors, like religious belief (Sun et al 2018), marital status (Agho et al 2010), ethnicity and physical conditions (Werg et al 2013), have been seen significant in analysing landslide risk attitudes.…”
Section: Introductionmentioning
confidence: 99%